2018
DOI: 10.1108/jaee-09-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Public accounting vs private accounting, career choice of accounting students in China

Abstract: Purpose Built upon three components (attitudes, subjective norms, and perceived behavioral control) of the theory of planned behavior (TPB), the purpose of this paper is to analyze the factors that influenced accounting students’ intention to pursue public accounting instead of private accounting as their career choice in China. Design/methodology/approach The TPB is used to predict the rational intention of accounting students in this study. A binary logistic regression analysis was applied to test all hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
22

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 40 publications
8
43
0
22
Order By: Relevance
“…This was compounded by low financial rewards relative to the workload given. This is in line with Wen et al (2018) stating that with their less excellent knowledge, the public accountants felt unable to deal with such a high workload.…”
Section: None Selfemployedsupporting
confidence: 80%
See 1 more Smart Citation
“…This was compounded by low financial rewards relative to the workload given. This is in line with Wen et al (2018) stating that with their less excellent knowledge, the public accountants felt unable to deal with such a high workload.…”
Section: None Selfemployedsupporting
confidence: 80%
“…the number of accounting graduates is huge annually. Unfortunately, the ones who select public accounting profession is quite small (Yuliansyah & Suryani, 2016).Previous studies indicated that intention in being a public accountant is influenced by the common perception of the accounting profession as boring and tedious (Sugahara et al, 2008), high workload (Omar et al, 2015), low financial reward (Wen et al, 2018), low job satisfaction, and high employee turnover (Suryani et al, 2018).This results in concerns with regard to the accounting profession in the future, especially in the digital era. Professional sustainability is a hot topic discussed by accountants (Alimbudiono & Suhartini, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of transformational leadership, that to be connected with, for positive organizational outcomes. It focuses on the process of building employee trustworthiness to meet the organizational vision, mission, strategies, objectives by the leader [13].…”
Section: Discussion: (Literature Results)mentioning
confidence: 99%
“…Dalam hal memilih karier akuntansi, sikap didefinisikan sebagai evaluasi keseluruhan mahasiswa tentang keinginan memilih profesi akuntan sebagai karier mereka (Wen et al, 2018). Ketika seorang mahasiswa memiliki suatu keyakinan bahwa suatu perilaku dapat menghasilkan hal yang positif, sikap mereka terhadap perilaku tersebut cenderung akan menguntungkan.…”
Section: Pendahuluanunclassified